About rearranged during transfection in non-small cell lung cancer - Gridelli, Cesare; Losanno, Tania (Translational Cancer Research; Vol 6, Supplement 7 (October 24, 2017): Translational Cancer Research, 2017)
Lung cancers represent a more large landscape than well-known histological categories including lung adenocarcinoma (45% of cases), squamous cell carcinoma (25%), large cell carcinoma (10%) and small cell lung carcinoma (20%). Since 2004, when epidermal growth factor receptor (EGFR) mutations were discovered to give sensitivity to tyrosine kinase inhibitors (TKIs) in lung adenocarcinomas, developments had showed that lung cancer are molecularly distinct with different therapeutic vulnerabilities (1).